PENGARUH JAMINAN SOSIAL DAN LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN DI PT EKSPLORASI NUSA JAYA KABUPATEN MIMIKA - Edowardus Renyaan; Habel Taime (Adisam Publisher, 2025)
This study aims to analyze the effect of social security and work environment on employee morale at PT Eksplorasi Nusa Jaya, Mimika Regency. The research employed a quantitative method with an associative approach. The population consisted of 96 employees, while a sample of 47 respondents was selected using the Slovin formula. Data were collected through questionnaires and observations, and subsequently analyzed using multiple linear regression with the assistance of SPSS. The results indicate that social security has a positive and significant effect on employee morale. Similarly, the work environment also exhibits a positive and significant influence on employee morale. Simultaneously, both variables affect employee morale, as reflected by the F-test value of 49.575 and a significance value of 0.000, demonstrating that social security and work environment jointly have a positive and significant impact on employee morale. These findings reinforce the view that companies providing adequate social security and fostering a conducive work environment can enhance employee motivation and productivity.